ARTICULATION MODELS – CORRECTION TOOLS OF CHILDREN SOUND PRONUNCIATION DISTURBANCES IN PRE-SCHOOL AGE - Miltiņa, Irēna; Augstkalne, Dace (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
Sound pronunciation disturbances are one of the frequent speech problems observed in pre-school age, that is why there are developed different methods in correction methodology and one of them is approach by using sound articulation models. They help for a child in pre-school age to acquire meaningfully the physiological basis of sound pronunciation and allow being an active participant in correction process.